Shakespeare During Covid-19: Expanding Our Theatrical Horizons - Méline Dumot (Sillages Critiques)
This article focuses on the digital adaptations of Shakespeare’s plays which have been produced and/or broadcast during the Covid-19 pandemic. It reflects on three assumptions in particular: that digital theatre is not “real” theatre, that audiences were not active participants during these online performances, and that digital theatre was a simple parenthesis which would close as soon as theatres would open again. I argue that, on the contrary, online theatre has taught us about the limitations of physical theatre and should inspire us to make it more accessible. Shakespeare’s plays appear as an experimental ground to implement these changes.